2020
DOI: 10.3390/ijerph18010183
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Respiratory Effects of Air Pollution from Biomass Cookstoves on Pregnant Women in Rural India

Abstract: Background: In India, biomass fuel is burned in many homes under inefficient conditions, leading to a complex milieu of particulate matter and environmental toxins known as household air pollution (HAP). Pregnant women are particularly vulnerable as they and their fetus may suffer from adverse consequences of HAP. Fractional exhaled nitric oxide (FeNO) is a noninvasive, underutilized tool that can serve as a surrogate for airway inflammation. We evaluated the prevalence of respiratory illness, using pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Recent evidence suggests that residential proximity to industry, exposure to second-hand smoke (SHS), inappropriate indoor environment, and use of biomass cooking fuel were associated with sleep disturbance [14][15][16][17][18][19][20][21][22][23]. Biomass cooking fuel is a well-known risk factor for several chronic respiratory and cardiac diseases [24,25]. In developing countries like India, a large proportion of the population who are at the lower bar in the socioeconomic status does not have a separate kitchen and has to cook inside the living room area using biomass fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that residential proximity to industry, exposure to second-hand smoke (SHS), inappropriate indoor environment, and use of biomass cooking fuel were associated with sleep disturbance [14][15][16][17][18][19][20][21][22][23]. Biomass cooking fuel is a well-known risk factor for several chronic respiratory and cardiac diseases [24,25]. In developing countries like India, a large proportion of the population who are at the lower bar in the socioeconomic status does not have a separate kitchen and has to cook inside the living room area using biomass fuel.…”
Section: Introductionmentioning
confidence: 99%
“… 42 Another study conducted in India confirmed that biomass fuel has adverse respiratory impact e.g., dyspnoea and airway inflammation on pregnant women. 43 A recent study conducted in Ghana also found a positive association between inhalation of CO discharged from burning biomass fuel and prolonged coughing, wheezing, phlegm, and other respiratory infection 44 Similarly, one more study in Ghana observed effects of CO on birthweight, birth length, and gestational age. 31 The findings from the study suggested for the neonates born to mothers without reported placental malaria, each 1 ppm increase in CO was associated with reduced gestational age (−0.5 days [95% CI: −1.3, 0.2 days]), birthweight (−38.7 g [95% CI: −66.2, −11.1 g]), birth length (−0.3 cm [95% CI: −0.5, −0.02 cm]).…”
Section: Discussionmentioning
confidence: 97%
“…Several recent reviews have found strong evidence linking HAP to various respiratory infections, chronic lung illnesses, cardiovascular disorders and respiratory cancers (Gordon et al, 2014;Mortimer et al, 2012;Smith, 2000). A study which evaluated the prevalence of respiratory illness, using pulmonary questionnaires and fractional exhaled nitric oxide (FeNO) measurements (a non-invasive biomarker of inflammation that can help to better understand the physiologic effects of biomass smoke on pregnant women), among pregnant women found that FeNO levels were higher in the biomass versus LPG group (25.4 ppb vs. 8.6 ppb; p value = .001), and increased FeNO levels and higher dyspnoea scores in biomass-fuel-exposed subjects confirm the adverse respiratory effects of this exposure during pregnancy (Parikh et al, 2020).…”
Section: Household Air Pollution and Respiratory Diseasementioning
confidence: 88%